Analysis of the application of the SCRUM method to the development of the SITASI: final project management application - Denny Jean Cross Sihombing (Institute of Computer Science (IOCS), 2023)
This study examines the application of the Scrum methodology in developing a Final Project Management Application, known as SITASI, which serves as a platform for students and supervisors to manage and monitor all processes related to final projects or theses. The research question evaluates how Scrum influences development efficiency, application quality, and user satisfaction in this context. The research utilizes a software development analysis to comprehensively understand and plan the project before commencing the development process. The study aims to design a tailored solution that aligns with user expectations by identifying user needs and potential challenges. Result of this research, the study emphasizes the significance of team and technology factors in driving the adoption of Scrum in developing the SITASI application. The findings suggest that effective teamwork and leveraging appropriate technological tools like Scrum can positively impact the application's development process. While individual and organizational factors did not significantly influence, the study highlights the importance of a conducive work environment for successful application development. By understanding these factors, developers, and stakeholders can make informed decisions to enhance the implementation of Scrum and improve the efficiency and quality of the final project management application, SITASI.